2007
DOI: 10.1063/1.2434251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sheared flow on magnetic islands

Abstract: The effect of sheared flow on a magnetic island is examined. In contrast to the density and temperature gradients which are flattened for sufficiently wide islands, it is found that the velocity gradient persists inside the separatrix whenever the constant-approximation is satisfied. It follows that velocity shear has a negligible effect on island amplitude in that approximation. The effect of the violation of the constant-approximation is explored by using the Kelvin-Stuart family of islands, and it is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…23,45 Here the relevant plasma flow is E ϫ B which makes the local radial electric field E r zero, i.e., E ϫ B = 0 in a frame going at this rotation; this is usually dominated by toroidal rotation and is identically the same for electrons, main ions, and any impurity ions. The island flow in the laboratory frame is thus, if viscosity dominates, ⍀ ,lab Ϸ n⍀ i + ⍀ i ‫ء‬ where ⍀ i is the toroidal plasma flow angular frequency ͑from CER of CVI for example as here on DIII-D͒ and ⍀ i ‫ء‬ is the ion diamagnetic drift frequency in the codirection for the usual profiles and directions.…”
Section: Sign Dependence or Offset In Flow Shear Effect On ⌬ј?mentioning
confidence: 99%
“…23,45 Here the relevant plasma flow is E ϫ B which makes the local radial electric field E r zero, i.e., E ϫ B = 0 in a frame going at this rotation; this is usually dominated by toroidal rotation and is identically the same for electrons, main ions, and any impurity ions. The island flow in the laboratory frame is thus, if viscosity dominates, ⍀ ,lab Ϸ n⍀ i + ⍀ i ‫ء‬ where ⍀ i is the toroidal plasma flow angular frequency ͑from CER of CVI for example as here on DIII-D͒ and ⍀ i ‫ء‬ is the ion diamagnetic drift frequency in the codirection for the usual profiles and directions.…”
Section: Sign Dependence or Offset In Flow Shear Effect On ⌬ј?mentioning
confidence: 99%
“…Differential rotation has generally a stabilizing effect on the growth of magnetic islands. However, it has been reported that shear flow has only limited impact on the stability of magnetic islands for a fully relaxed equilibrium (Waelbroeck, Fitzpatrick & Grasso 2007). A potentially interesting case for future considerations is the situation when the differential rotation is fast enough to match the local poloidal Alfvén speed, so that singular currents develop at those Alfvén resonances (Wang et al 1998).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Third, the shear in the local flow profile can directly modify the plasma flow and current patterns in the immediate vicinity of the island. 18 This effect, which can only be calculated from nonlinear theory, is far less completely understood than the other two. It is predominately associated with E ϫ B flow shear, since E ϫ B flow generates an ion polarization current in the vicinity of the island, whereas parallel flow does not drive any such current.…”
Section: Introductionmentioning
confidence: 99%